Systematic monetary policy and the macroeconomic effects of shifts in residential loan-to-value ratios - Bachmann, Ruediger; Rüth, Sebastian (International economic review, 2020)
What are the macroeconomic consequences of changing aggregate lending standards in residential mortgage markets, as measured by loan-to-value (LTV) ratios? Using a structural vector autoregression (VAR), we find that GDP and business investment increase following an expansionary LTV shock. Residential investment, by contrast, falls after a small initial uptick, a result that depends on the systematic reaction of monetary policy. We show that, historically, the Fed tended to respond to expansionary LTV shocks by raising the monetary policy instrument, and, as a result, mortgage rates increased and residential investment declined. House prices are affected in a similar manner.